IMPLEMENTASI BALANCED SCORECARD DALAM PENGUKURAN KINERJA MANAJEMEN BERBASIS SEKOLAH DI MADRASAH DINIAH TAKMILIAH AWWALIAH DESA SUKASENANG. - Ari Samsul Bahri (Program Studi Manajemen Pendidikan Islam, 2022)
This paper aims to determine the effectiveness in the management of Madrasah using balanced scorecard performance analysis, including using four perspectives, finance, customers, internal business processes and learning and growth in the Madrasah. This research uses a qualitative approach with a descriptive model. Based on research that has been done, it is known that the management of the Madrasah with a balanced scorecard approach is categorized as good. Because the measurement in four perspectives is close to the expected target. After being measured by the balanced scorecard approach and then analyzed with the effectiveness indicators according to Danim, the results obtained by the management of the Jam'iyyah Islamiyyah Islamic boarding school can be said to be effective. Keywords: Effectiveness, Madrasah Management, Balanced Scorecard